Pre-Occupancy Evaluation of Affective Experiences in Building Information Modeling Through SLR and an e-Delphi Survey - Balamaheshwaran Renganathan; Radhakrishnan Shanthi Priya; Ramalingam Senthil (Technologies)
Building information modeling (BIM) is increasingly used during the conceptual design phase, which focuses on simulations such as energy usage analysis and comfort levels, like temperature and lighting conditions, to enhance user experience and well-being, which are key factors for meeting Sustainable Development Goal 3. This study employs a systematic literature review and an e-Delphi survey to explore how a pre-occupancy evaluation integrated within BIM frameworks addresses affective responses and suggests ways to improve design decisions that align with the UN’s sustainable development goals. The study identified a research gap in how BIM evaluations are conducted during the conceptual design stage, including crucial sensory aspects for human well-being. The research suggests incorporating evidence-based design instruments like body sensor networks (BSN) and immersive virtual reality and methods like neurophenomenology to enhance the assessment of user interactions in the design process. Prioritizing the human-centered design approach right from the start can facilitate the integration of innovative workflows into architecture, engineering, and construction practices. Overcoming resistance to these workflows and methodologies is essential for advancing BIM’s role in fostering spatial environments that support health, well-being, and positive affective experiences.